A spatially non-overlapping dual-wavelength 2D FBG for the measurement of temperature and strain - Che, Zonglun; Wang, Jun; Xu, Pan; Gu, Xijia; Ma, Lina; Zhu, Jing; Cao, Chunyan (Frontiers in Physics, 2022)
This work designed a dual-wavelength 2D fiber Bragg grating (FBG) engraved on the single-mode fiber to measure the temperature and strain. The FBG is composed of two sub-gratings that are not overlapped spatially at the same location of the fiber core. Experiments showed that the temperature and strain of this grating were separately measured to be 10.64pm/°C and 0.882731pm/uε at the central wavelength of 1548nm, and 10.74pm/°C and 0.916080pm/uε at the central wavelength of 1550nm. These coefficients constitute a coefficient matrix that can solve the problem of cross sensitivity between temperature and strain, which has been verified by varying central wavelengths caused by the synchronous change of temperature and strain.